(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a concise overview of the history of Uzbekistan, tracing its journey from ancient times through to the modern era. Key historical periods covered include the influence of early empires, the significance of the Silk Road, the impact of Islamic culture, the Mongol invasion, and the Timurid dynasty’s contributions. The narrative follows Uzbekistan’s transition from fragmented khanates to becoming part of the Russian Empire, and then under Soviet rule, leading to its eventual independence in 1991. The modern period is highlighted by economic development, social and political reforms, and efforts to preserve cultural heritage. The country’s rich architectural legacy, traditional arts, and diverse cuisine are also discussed, emphasizing Uzbekistan’s unique position as a cultural and historical crossroads in Central Asia.